(3MGTjI Ydi GdeWdY TQM GjSGZhLj dRcQjG GdCfUGQjs - (3GdbdjhHj GdCRgQj, CHh GdYHGS, TgGH GdOjf, CMeO Hf CMeO Hf SdGeI, (B1069 (3g`s ((3MSfs)
(3ChdgG (B:s
(3HYO GdHSedI Cf Chdi eG fWb Hg GddSGf hHYO agPG eG JjSQ JYdjbg ef GdahGFO Ydi TQM GjSGZhLj ddEeeGe RcQjG GdCfUGQj TjN GdESdGes
(3BNQgG (B:s
(3hgj ddNWGHI heNHdGJ hgj heTHgGJ jYjOgG hgj ddeZGdWI hCeG GdGSJbQGA Gh GdJeKjd ageG edMbGf HGdHQgGf aj GdMce hGdJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 92s
(3eYLe GdeDdajf (B1 / 94s
(3gOjI GdYGQajf (B1 / 161s
(3GdecJHI GdCRgQjI (B1 / 384s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs